(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article considers the cultural concept «Icon», as a cognitive immanent system of intertexual verbal and nonverbal cultural codes of the Orthodox consciousness, which reveals the spiritual originality of the Slavic people.